Evolutionary biology : self/nonself evolution, species and complex traits evolution, methods and concepts - Pontarotti, Pierre (Springer, 2017)
This book presents 19 selected contributions to the 20th Evolutionary Biology Meeting in Marseille, which took place in September 2016. They are grouped under the following major themes: · Self/Nonself Evolution · Species Evolution and Evolution of Complex Traits · Methods and Concepts The aims of the annual meetings in Marseille - which bring together leading evolutionary biologists and other scientists using evolutionary biology concepts, e.g. for medical research - are to promote the exchange of ideas and to encourage interdisciplinary collaborations. Offering a revealing overview of the latest findings in the field of evolutionary biology, this book represents an invaluable source of information for scientists, teachers and advanced students alike.
Keywords: Evolution (Biology) -- Congresses.; Molecular evolution -- Congresses.; Evolutionary genetics -- Congresses.; elektronické knihy; electronic books